BANTUAN LOGISTIK KEPADA KORBAN BENCANA ALAM YANG TERKENA GEMPA BUMI DI DESA CIPUTRI KECAMATAN PACET CIANJUR JAWA BARAT - Sumatirta, Edi; Naim, Abu; Hadi, Helmas Septiyo; Wulandari, Sisca; Istiyono, Yogi Priyo (STAI Darul Qalam Tangerang, 2023)
Indonesia's geographical conditions are included in natural disaster-prone areas. Indonesia itself is located in the Ring of Fire on Pacific Rims, which often results in earthquakes, landslides, volcanic eruptions, and tsunamis. The Ring of Fire on Pacific Rims itself is home to active volcanoes in the world and about 90% of the places where earthquakes occur. About 13% of the total number of volcanoes in the world are in Indonesia, including 500 volcanoes with inactive status, and 129 volcanoes with active status, have a large enough eruption potential to reach 60% of the number of volcanoes scattered, besides having a horseshoe-like shape and can cover an area of 40,000 km (Gosal et al., 2018). Natural disasters that occur certainly have an impact on people's homes which are also destroyed. Many people were killed, injured, and lost their homes.The implementation of this community service received a grant from the Muhammadiyah Disaster Management Center (MDMC) PP Muhammadiyah which will be distributed to victims of natural disasters in one of the earthquake disaster locations in Cianjur, by distributing logistics this community service activity is designed so that Lecturers of Muhammadiyah A.R Fachruddin University Tangerang can carry out the obligations of the Chess Dharma of Higher Education and can help the Cianjur community in overcoming trauma after the earthquake natural disaster in November 2022